Pengaruh Kualitas Pelayanan terhadap Kepuasan Pelanggan di Hotel Pyramid Suites Banjarmasin - Fairuz, Iyut (Jurnal Ilmiah Global Education, 2024)
Banjarmasin is a unique city nicknamed the City of a Thousand Rivers. This uniqueness is what causes many entrepreneurs to come to open businesses, one of which is a hotel business. The recommended hotel in Banjarmasin is the Pyramid Suites Hotel. Because apart from having good quality products and services, this hotel has also received many awards from various online hotel booking applications. Therefore, researchers are interested in further researching the Pyramid Suites hotel in Banjarmasin with the aim of analysing the influence of service quality on guest customer satisfaction at the Pyramid Suites Banjarmasin hotel. This study aims to analyse and describe how much influence service quality has on customer satisfaction. This type of research is quantitative, with a conclusive causal approach, namely research that aims to obtain a conclusion from the data that has been obtained and processed which explains the causal relationship between the variables. The population in this study are members of Hotel Pyramid Suites, namely guests who stay more than three times. research sample as many as 100 respondents. The data collection technique used a questionnaire which was then used as a score tabulation for each variable studied. The data analysis method used in this study is Smart PLS 3. The results showed that the quality of service which consists of variables of physical evidence, reliability, responsiveness, assurance and empathy affect customer satisfaction.